Impact of Chronic Kidney Disease on Brain Structure and Function - Steinbach, Emily J.; Harshman, Lyndsay A. (Frontiers in Neurology, 2022)
Chronic kidney disease (CKD) affects more than 37 million American adults. Adult-onset CKD is typically attributed to acquired comorbidities such as aging, type II diabetes, and cardiovascular disease. Conversely, congenital abnormalities of the kidney and urinary tract are the most common cause of CKD in children. Both adult and pediatric patients with CKD are at risk for neurocognitive dysfunction, particularly in the domain of executive function. The exact mechanism for neurocognitive dysfunction in CKD is not known; however, it is conceivable that the multisystemic effects of CKD—including hypertension, acidosis, anemia, proteinuria, and uremic milieu—exert a detrimental effect on the brain. Quantitative neuroimaging modalities, such as magnetic resonance imaging (MRI), provide a non-invasive way to understand the neurobiological underpinnings of cognitive dysfunction in CKD. Adult patients with CKD show differences in brain structure; however, much less is known about the impact of CKD on neurodevelopment in pediatric patients. Herein, this review will summarize current evidence of the impact of CKD on brain structure and function and will identify the critical areas for future research that are needed to better understand the modifiable risk factors for abnormal brain structure and function across both pediatric and adult CKD populations.